Level of Wear Occurring on the Long Arm due to Friction with Palm Kernel Shells in the Digester Machine - Dejoi Irfian Situngkir; Sitorus, Fransnazoan; M. Rahmad Hidayat Panggabean (LPPM Politeknik Aceh Selatan, 2024)
A digester is a piece of equipment consisting of a cylindrical tube with both long and short knives. This tool is used to aid the processing by slicing and stirring, making the fruit soft. Common issues with digesters usually involve wear and breakage of the digester knives. Wear is generally understood as the loss of material due to the mechanical interaction between two moving and loaded surfaces. Wear can disrupt the production process, affecting the company's productivity. The objective of this research is to determine the volume and rate of wear on the long arm of a cast steel digester. Based on this study, the wear value obtained for the long arm digester is a wear volume of 19,117,969 mm³ and a wear rate of 9,558.984 mm³/hour under a load of 23,520 N over 2,000 hours of operation. This indicates that the replacement of the long arm digester should be performed according to the specified operational time limits while considering the load entering the digester, in order to prevent a decrease in the company's productivity.